Hernia Nukleus Pulposus - Liza Berlina; Ichwanuddin Ichwanuddin (Termometer: Jurnal Ilmiah Ilmu Kesehatan dan Kedokteran, 2024)
Anatomically the waist is the area of ​​the L1 spine to the sacrum and the muscles around it. The waist area has an important function in the human body, namely making the body stand upright, movement, and protecting several important organs in it. Hernia nucleus pulposus (HNP) is a disease, where the soft pad between the vertebrae (soft gel disc or nucleus pulposus) experiences pressure in one of the posterior or lateral parts so that the nucleus pulposus ruptures and falls out so that there is a protrusion through the annulus fibrosus into the spinal canal and causes compression of the nerve roots. The diagnosis of HNP can be confirmed by anamnesis, physical examination and several supporting examinations such as plain lumbosacral photos, CT scans, and MRI as the gold standard for diagnosing HNP because it can detect the location of compression of the spinal cord and caudaequina